The Development of Android-Based Learning Media in Computer and Basic Network Lessons Class X TKJ Cokroaminoto Vocational High School, Kotamobagu - Pelealu, Ray Rivay Anugrah Aer; Oroh, Rolly Robert; Rompas, Parabelem T.D (International Journal of Information Technology and Education, 2023)
Cokroaminoto Kotamobagu Vocational School is an educational institution that aims to develop the potential of the nation's children so they can compete at the world level. To fulfill these objectives, educational institutions need to be equipped with adequate computer networks. This study aims to develop learning media based on Android (m-learning) on the subject of Applying IP Addressing to Computer Networks for class X SMK Cokroaminoto Kotamobagu. The research method used in this research is research and development (R&D). The steps taken are Potential and Problems, Gathering Information, Product Design, Design Validation, Design Improvement, Product Trials, Revision of potentials and problems, data collection, product design, design validation, design revisions, product trials, and product revisions. After the product trials were carried out with two stages, namely small group trials carried out by twelve students, and wide trials carried out twice, the first stage was carried out by one teacher, and the second stage by thirty-four participants educated. From the product trials, the results regarding the android-based m-learning application in the material Applying IP Addressing on Computer Networks obtained an assessment with very feasible criteria based on the teacher's assessment and very interesting based on the student's assessment.